Minnesota - Hintz, Martin (New York : Children's Press, 2000)
Describes the geography, plants, animals, history, economy, language, religions, culture, sports, art, and people of the state of Minnesota.
ch. 1. ch. 2. ch. 3. ch. 4. ch. 5. ch. 6. ch. 7. ch. 8. ch. 9. ch. 10. What's in a name -- First Minnesotans -- Dawning of a new age -- Changing times -- Water, winter, woods -- Cities as varied as the landscape -- Progressive government -- Timber, wheat, and tourism -- Diverse group -- "Where all the women are strong".
Includes bibliographical references and index.
Keywords: Minnesota -- Juvenile literature